Sytuacja ekonomiczna gospodarstw rolnych krajów Unii Europejskiej w zależności od ich potencjału produkcyjnego - Poczta, Walenty; Kita, Katarzyna; Średzińska, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The aim of this paper was to determine the situation of the EU farms in 2009 according to their production potential and to identify changes of the situation compared to 2004. FADN data was used in the paper. Then, grouping farms was conducted by means of cluster analysis. For clusters separated on farm’s equipment with production factors the financial indicators and income per farm and per employee were calculated. A more favourable income situation occurs in farms with a more correct relations between the resources of capital and other production factors, although the financial situation of those entities assessed on the basis of financial indicators is not always clearly favourable.